A panda is born [videorecording (DVD)] ; and Baby panda's first year - Friedman, Lisa; Derek, Bo (Animal Planet ; Genius Entertainment, 2008)
A panda is born: Documents two seasons of panda mating at the Smithsonian National Zoo.